O ensaio no romance de Saramago: a experiência humana sob o crivo da palavra - Christal, Wendel Cássio (2017)
In contemporary literature, the frontiers between literary genres, as well as the frontiers between literature and other genres of other areas, are becoming more and more tenuous, appearing as a kind of hybridity impelled by the dynamics of discourses, constantly changing. Appearing in the most diverse fields of knowledge, the essay has always been present in the field of sciences, especially in Philosophy, mainly from Montaigne, as well as in literature, with Francis Bacon, in which it usually receives the title of "literary essay". However, research on the role of literary criticism in Portuguese and the implications of the essay as a genre for theory of literature and literary production, able to comprehend the intrinsic aspects of the essay, is lacking, as well as an understanding on the essay as a genre or discoursive domain able to unite different subgenres from the frontiers between literature and philosophy, or even science itself. This thesis, by means of a hermeneutic methodology, aims to investigate the essay as an inherent element of the work of the Portuguese writer José Saramago, with emphasis on the following works: Claraboia (2011) and The intermittences of death (2014). This choice contrasts two distinct phases of the literary production of the writer: the beginning and the end of his career, in order to verify to what extent essayistic procedures are plotted in the literary prose of the author in these two distinct phases, before and after The Statue and the stone (2013). In such works, as well as in all the running of his literary production, aspects and procedures stand out in relation to the aesthetic elements of the essay. In order to discuss and analyze such questions in the work of Saramago, we will prioritize, as theoretical reference, fundamental authors of the field of philosophy that deal with the essay: Montaigne, George Lukács, Max Bense, Theodor Adorno, João Barrento, as well as other contemporary authors in the field of literature and philosophy. Thus, in combining essay and novel, in an experimental, singular and always ironic way, Saramago obtains a powerful support to reinvent reality, in the sense of representing, under the sieve of the word, the human condition, giving the novel an artistic dimension of essentially critical aspect, an essayistic aspect.